Epidemiological insights into Shigella infections in Ethiopia: a study of prevalence, antimicrobial resistance, and associated factors - Mihret Teshale, Amete; Abrha Kalayu, Alem; Tigabu Seyoum, Eyasu; Erku Abegaz , Woldaregay (International Journal of Infection Control, 2026)
Objective: The aim of this study was to assess the prevalence of Shigella infection, its antimicrobial resistance patterns, and associated risk factors among diarrheal patients in Ethiopia. Method: A cross-sectional study was conducted from October 2021 to November 2022 among 2,331 diarrheal patients from Addis Ababa, Gondar, and Harar. Data on socio-demographics and clinical characteristics were collected using a structured questionnaire and REDCap software. Stool samples were processed using standard microbiological methods, and Shigella isolates were confirmed by polymerase chain reaction. Antibiotic susceptibility testing was performed using the Phoenix M50 machine. Data analysis was conducted in R software, employing univariable and multivariable logistic regression to identify associated factors. Result: This study indicated that the prevalence of Shigella spp. was 2.79%, highest in Harar (5.05%) and lowest in Addis Ababa (0.88%). Being resistance to ciprofloxacin (43.08%) and azithromycin (32.31%), key antibiotics recommended for shigellosis treatment are alarmingly high across study sites. The resistance to at least one antibiotic was shown by 98.46% of the isolates, with 33.85 and 73.85% being extended-spectrum beta-lactamase (ESBL) producers and multidrug-resistant (MDR), respectively, and showed significant variation among study sites. Harar had the highest odds of Shigella infection compared to Addis Ababa [AOR: 1.39, 95% CI: 1.02, 1.57] and Gondar [AOR: 1.12, 95% CI: 1.01, 1.24], while Gondar had higher odds than Addis Ababa [AOR: 1.15, 95% CI: 1.09, 1.35]. Households with unimproved water sources and unimproved sanitation showed higher odds of Shigella infection [AOR: 1.99, 95% CI: 1.17, 3.01, P = 0.03] and [AOR: 1.39, 95% CI: 1.27, 1.74, P = 0.03], respectively. Conclusion: In conclusion, Shigella infections in Ethiopia exhibit high ESBL and MDR rates, emphasizing the need for improved sanitation, water safety, and antibiotic stewardship.